Addressing competency requirements of social work students during the COVID-19 pandemic in Malaysia. Issue 8 (16th November 2020) - Azman, Azlinda; Singh, Paramjit Singh Jamir; Parker, Jonathan; Ashencaen Crabtree, Sara
ABSTRACT: COVID-19 resulted in massive disruption and changes in every aspect of our lives. To curb the spread of the virus, many governments limited the movement of people or imposed full 'lockdowns'. This created significant challenges for social workers practising with people often reliant on interpersonal support such as those at risk of domestic abuse; with mental health problems or learning disabilities. Measures to reduce viral spread affected the education sector at all levels from pre-school to higher education, disrupted traditional classroom pedagogy and shifted to technologically supported e-learning to minimise disruption to the students' education. In lockdown, online teaching has become the new norm. E-learning has its limitations for professional curricula such as social work. Like most countries, field practice represents a compulsory component of the social work curriculum in Malaysia which measures the capabilities or competency of students to enable them to become qualified social workers. When COVID-19 forced universities and agencies to halt field placements in Malaysia, the immediate challenge was to find alternative ways of assessing students. This paper aims to provide an overview of field education assessment in Malaysia during the pandemic and to pose questions for future assessment as Malaysian social work drives towards increased professional regulation.